노인의 디지털 리터러시와 인지기능의 관계에서 사회적 활동 참여의 조절효과 - 노미영(Mi-Young Roh) (한국콘텐츠학회 논문지, 24(5), 2024)
본 연구는 노인의 디지털 리터러시가 인지기능에 미치는 영향을 확인하고, 디지털 리터러시와 인지기능 간 관계에서 사회적 활동의 조절효과를 검증하고자 한다. 이를 위해 2020년도 노인실태조사에 응답한 대상자 중 65세 이상 노인 9,920명의 자료를 활용하였으며, 디지털 리터러시는 독립변수, 인지기능은 종속변수, 사회적 활동 유무는 조절변수로 설정하고 SPSS 29.0을 사용하여 위계적 회귀분석을 시행하였다. 그 결과, 사회적 활동에 참여하지 않는 노인이 사회적 활동에 참여하는 노인보다 전반적으로 인지기능이 낮았으며, 노인의 디지털 리터러시는 인지기능에 정적인 영향을 미치는 것으로 나타났다. 노인의 사회적 활동 유무는 디지털 리터러시와 인지기능의 관계에서 유의한 조절효과가 있음을 검증하였으며, 이는 디지털 리터러시가 인지기능에 미치는 영향이 사회적 활동을 하는 집단에 비해 사회적 활동을 하지 않는 집단에서 더욱 큰 것을 의미한다. 이러한 결과를 토대로 디지털 정보화 사회에서 노인의 인지기능을 높이기 위해 디지털 리터러시 교육의 활성화 및 다양한 사회적 활동 참여의 확대 방안 또한 함께 고려할 필요가 있음을 제언한다. The purpose of this study was to examine the impact of digital literacy on cognitive function in the elderly and verify moderating effect of social activities on the relationship between digital literacy and cognitive impairment. Data from 9,920 self-respondents in the 2020 Korean Elderly Survey were used. Digital literacy was set as the independent variable, cognitive function as the dependent variable, and social activities as the moderate variable and hierarchical regression analysis was performed using SPSS 29.0. As a results, elderly people who did not participate in social activities had lower overall cognitive function than those who participated in social activities, and digital literacy was found to have a positive effect on cognitive function. Lastly, the social activities of the elderly showed a significant moderating effect in the relationship between digital literacy and cognitive function which means that the impact of digital literacy on cognitive function is greater in the socially inactive elderly group than in the socially active elderly group. Based on these results, it is necessary to expand digital literacy education in the digital information society and consider ways to participate in various social activities to improve cognitive function of the elderly. KCI Citation Count: 0